The Effects of Music Listening with Play on Preference, Recognition of the Main Melody and Musical Creativity in Elementary School Students - Hwang, Eunyoung (Voices: A World Forum for Music Therapy, 2011)
The purpose of this study was to examine the effects of a classical music listening program, namely music listening with plays, for elementary grade one students on music preference, recognition of the main melody, and musical creativity. The classical music listening program organized for this study employed various musical experiences such as singing, playing, composing and moving. The participants of this study were 61 elementary grade one students from Kyong-gi Province, Korea, who attended the classical music listening program after school. The students were divided into the two groups, experimental and control, which consisted of 31 and 30 students respectively. The experimental group participated in a music listening program with plays for 12 sessions, while the control group participated in a passive music listening program for 12 sessions. The results revealed a significant difference between the two groups in terms of preference and recognition of the main melody. Further, there was a significant difference in their musical creativity.